The Paradox of Profitability Amidst Oversupply: Investor Responses to Performance and Capital Structure in the Cement Industry - devina mahdalita; Fanlia Prima jaya; Akhmad Aspiannor (Hut Publication Business and Management, 2026)
The cement industry in Indonesia faces severe structural challenges due to chronic domestic market oversupply and skyrocketing energy costs post-pandemic. This study aims to analyze the influence of Capital Structure and Profitability on Firm Value in cement sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2024 period. The research method used is descriptive with a quantitative approach. The research sample was selected using a purposive sampling technique that resulted in five main companies: PT Indocement Tunggal Prakarsa Tbk, PT Solusi Bangun Indonesia Tbk, PT Semen Baturaja Tbk, PT Waskita Beton Precast Tbk, and PT Wijaya Karya Beton Tbk. Data analysis techniques include classical assumption tests and panel data regression analysis using the EViews 12 program. The results of the study show that partially, Capital Structure has a significant and positive effect on Firm Value (3.977 > table 2.052). Conversely, Profitability has a significant and negative effect on Firm Value (-2.237 > table 2.052), indicating a market paradox where short-term earnings efficiency fails to reflect long-term growth sustainability amidst industry saturation. Simultaneously, Capital Structure and Profitability have a significant effect on Firm Value with a Calculated F value of 7.669 > table 3.35. The value of the Coefficient of Determination R2 of 0.362 indicates that 36.2% of the variation in Firm Value can be explained by these two variables, while the remaining 63.8% is influenced by other factors outside the model.